STUDI PERSEPSI REMAJA PUTRI ATAS DIET BERDASARKAN GOLONGAN DARAH (Studi Kasus di SMA Kemala Bhayangkari 1 Medan) - Yulina Dwi Hastuty (Jurnal Pendidikan Kimia (JPKim), 2014)
Abstract. This study aims to determine how the image of young women knowledge about diet based on blood type in SMA Kemala Bhayangkari 1 . Given the many teenagers now are unknowingly living with unhealthy patterns . This is evidenced by the mortality of young is high enough . Most of the cause is of the food consumed . Influence on the blood type diet is great because they can affect the digestive system , decreasing the body 's metabolism and diseases such as kanker. This is a descriptive study , using primary data obtained via questionnaires . The population in this study were all young women m in classes 2  IPA in SMA Kemala Bayangkari I Medan . The results showed that the level of knowledge of adolescents are in the category of pretty but there is still much less knowledgeable ( 26.67 % ). Resources based on respondents who get information from health workers are still there as much less knowledgeable ( 28.12 % ) . Based on the mother's education is the higher education are much less knowledgeable (15.38 %). Based on the work of teenage mothers found that mothers work are less knowledgeable as much (46.15 %). Based on a healthy lifestyle are much less knowledgeable (38.46 %). It can be concluded that the source of information , mother's education , mother's occupation and lifestyle can affect young women knowledge about diet based on blood type . Key words : ladies student perception, diet based on blood type